The Protective Association between Pet Ownership and Depression among Street-involved Youth: A Cross-sectional Study. (2nd January 2016) - Lem, Michelle; Coe, Jason B.; Haley, Derek B.; Stone, Elizabeth; O'Grady, William
ABSTRACT: Street-involved youth represent a particularly vulnerable subsection of the homeless population and are at increased risk of health problems, substance abuse, and depression. Qualitative research has demon- strated that animal companions help homeless youth cope with loneliness, are motivators for positive change, such as decreasing drug or alcohol use, provide unconditional love without judgement, and improve youths' sense of health. To quantitatively investigate the association between depression and pet ownership among street-involved youth, a cross-sectional study was per- formed with a convenience sample of 189 street-involved youths who were surveyed in four cities in Ontario, Canada, 89 of whom were pet owners and 100 of whom were not. Logistic regression modelling found pet ownership to be negatively associated with depression in the study population (controlling for gender, regular use of drugs, and time since youth left home), with the odds of being depressed three times greater for youths who did not own pets. While pet ownership among street-involved youth has many liabilities, includ- ing impairing youths' ability to access shelter, services, and housing and employment opportunities, companion animals may offer both physical and psychosocial benefits that youth have difficult attaining. This finding highlights the importance of increased awareness among youth service providers of the potential impacts of pet ownership for street-involved youth.